Analysis of Loading and Unloading Productivity on Berth Utility at the Multipurpose Terminal Teluk Bayur Port - Cahyadi, Tonny Hendra; Sugiyono, Sugiyono (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The Purpose of this study is to analyze the ability of loading and unloading productivity and the time of ship berthing in influencing the berth utility at The Multipurpose Terminal Teluk Bayur Port. This study was designed with quantitative research methods for testing hypotheses using the regression analysis method of secondary data collected by 36 samples. The results of the study found that loading and unloading productivity and berthing time significantly of affected 71.3% on berth utility. The rest is done by controlling the ratio of effective time to berthing time so that it remains above 70% by reducing idle time and not operation time, so that berth utility is achieved according to the standard BOR that has been set.